A novel circulating miRNA panel for early differential diagnosis of pulmonary tuberculosis from lung cancer with similar radiographic presentations - Liu, Xiao; Wang, Wentao; Fu, Yurong; Yi, Zhengjun (Frontiers in Medicine, 2025)
This study aimed to establish a novel diagnostic approach based on a circulating microRNA (miRNA) panel to reliably distinguish pulmonary tuberculosis (PTB) from lung cancer (LC), particularly in patients presenting with overlapping radiographic features. A total of 592 participants were enrolled. In the discovery phase, miRNA expression profiles from 284 individuals, including PTB patients, LC patients, and healthy controls (HC), were analyzed to screen potential biomarkers. Candidate miRNAs were subsequently validated in an independent cohort of 308 plasma samples. The analysis revealed significant upregulation of hsa-miR-342-3p, hsa-miR-199a-3p, and hsa-miR-199b-3p in PTB compared with LC. A diagnostic panel incorporating these three miRNAs demonstrated robust performance, achieving an area under the receiver operating characteristic curve (AUC) of 0.911 (95% confidence interval [CI]: 0.852–0.952) in the training set and 0.886 (95% CI: 0.780–0.953) in the validation set, with a sensitivity of 0.879. This miRNA panel outperformed the World Health Organization -endorsed Xpert MTB/RIF assay, effectively identifying early-stage PTB cases without cavity formation. These findings underscore the potential of miRNA–based diagnostics as a non-invasive and highly accurate tool for differentiating PTB from LC in patients with comparable imaging presentations, addressing a critical gap in pulmonary disease management.